All-Optical Generation of Two IEEE802.11n Signals for 2 x 2 MIMO-RoF via MRR System - Amiri, I.S.; Alavi, S.E.; Fisal, N.; Supa'at, A.S.M.; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2014)
A radio-over-fiber system capable of very spectrally efficient data transmission and based on multiple-input multiple-output (MIMO) and orthogonal frequency-division multiplexing (OFDM) is presented here. Carrier generation is the basic building block for implementation of OFDM transmission, and multicarriers can be generated using the microring resonator (MRR) system. A series of MRRs incorporated with an add/drop filter system was utilized to generate multicarriers in the 193.00999-193.01001-THz range, which were used to all-optically generate two MIMO wireless local area network radio frequency (RF) signals suitable for the IEEE802.11n standard communication systems, and single wavelengths at frequencies of 193.08, 193.1, and 193.12 THz with free spectral range of 20 GHz used to optically transport the separated MIMO signals over a single-mode fiber (SMF). The error vector magnitude (EVM) and bit error rate of the overall system performance are discussed. Results show that the generated RF signals wirelessly propagated through the MIMO channel using the 2 × 2 MIMO Tx antennas. There is an acceptable EVM variation for wireless distance lower than 70, 30, and 15 m. It can be concluded that the transmission of both MIMO RF signals is feasible for up to a 50-km SMF path length and a wireless distance of 15 m.